The Discrete Institutional Changes of Nader Šāh and the Evaluation of the Economic Situation of Iran in the Afšārīd Era (Emphasizing the Constitutionalism Theory of Douglass North) - Esmaeil Ehsani (Alzahra University, 2021)
Regarding Nader Shah and his actions, historians have provided various and conflicting evaluations, yet the history of Nader Shah and his actions depict the picture of the temperaments and characteristics of the Iranian society inherited from from the Safavid period. There is no doubt that Nader Shah, as one of the most powerful generals of the war, was able to restore the Safavid Empire by the force of the sword and in the light of his military genius. Although Nader Shah's inevitable wars to expel the aliens and ensure security resulted in casualties to manpower and economic expenses, he ambitiously continued his conquests after punishing and expelling the aggressors. The twenty-one-year wars lead by him (1139-1160) with the Afghans, Ottomans, Indians, Bukhara Khanates, Khwarezm, and the internal arrogance destroyed human capital, ruined the country's wealth as well as destroying the trade centers, agricultural lands, economic centers and causing the spread of poverty. In fact, instead of devoting himself to improving agricultural infrastructure, developing business centers and increasing economic revenues to cover the costs of his wars, Nader undertook discrete institutional reformations in the Safavid institutions that increased governmental dominance over economic resources. This descriptive-analytical method, using the theory of institutionalism by Douglas North, evaluates the changes that Nader Shah made in the institutions left from the Safavid era and shows how his institutional changes affected the economic performance of the Afshari period. On the other hand, it examines the consequences of Nader Shah's policies on the agricultural and commercial situation of the Afshari era and explains the conditions of the economic activists of this period.